Positive interaction between melatonin and methyl jasmonate enhances Fusarium wilt resistance in Citrullus lanatus - Yan, Jingyi; Zhao, Tongshu; Chen, Yi; Liu, Haiheng; Wei, Chunhua; Ma, Jianxiang; Zhang, Yong; Yang, Jianqiang; Zhang, Xian; Li, Hao (Frontiers in Plant Science, 2025)
Fusarium wilt, caused by the soil-borne fungal pathogen Fusarium oxysporum (Fo), is widely recognized as one of the most devastating fungal diseases, inflicting significant damage on a wide range of agricultural and horticultural crops. Despite melatonin has recently emerged as a potential enhancer of plant resistance against Fo, the underlying mechanisms remain elusive. In this study, our results demonstrate that exogenous melatonin and MeJA enhance watermelon resistance against Fusarium oxysporum f. sp. Niveum race 2 (FON2) in a dose-dependent manner. The optimal concentration for melatonin and MeJA was determined to be 10 μM and 1 μM, respectively. Both melatonin and MeJA inhibited FON2 mycelial growth on PDA medium in a dose-dependent manner. Furthermore, exogenous melatonin significantly stimulated upregulation of MeJA synthesis genes and increased MeJA content upon FON2 infection. However, pretreatment with a MeJA synthesis inhibitor (DIECA) suppressed the induction of melatonin-induced resistance against FON2. Furthermore, MeJA also induced the upregulation of melatonin biosynthetic gene caffeic acid O-methyltransferase 1 (ClCOMT1) and increased melatonin accumulation in response to FON2. Notably, the reduction in FON2 resistance caused by ClCOMT1 deletion was completely restored through exogenous application of MeJA. These results suggest that melatonin facilitates MeJA accumulation, which provides feedback to promote melatonin accumulation, forming a reciprocal positive regulatory loop in response to FON2 infection. Additionally, polyphenol oxidase, phenylalanine ammonia lyase, and lignin are involved in the MeJA-induced resistance against FON2. The growing concern over minimizing pesticide usage and transitioning to sustainable and natural control strategies underscores the significant potential of such a mechanism in combating Fo.